Effect of Pathogenic Fungal Infestation on the Berry Quality and Volatile Organic Compounds of Cabernet Sauvignon and Petit Manseng Grapes - Li, Xueyao; Li, Tinggang; Li, Minmin; Chen, Deyong; Liu, Xiaowei; Zhao, Shanshan; Dai, Xiaofeng; Chen, Jieyin; Kong, Zhiqiang; Tan, Jianxin (Frontiers in Plant Science, 2022)
The effect of pathogenic fungal infestation on berry quality and volatile organic compounds (VOCs) of Cabernet Sauvignon and Petit Manseng were investigated by using biochemical assays and gas chromatography-ion mobility spectrometry. No significant difference in diseases-affected grapes for 100-berry weight. The content of tannins and vitamin C decreased significantly in disease-affected grapes, most in white rot-affected Petit Manseng, which decreased by 71.67% and 66.29%. The reduced total flavonoids content in diseases-affected grape, among which the least and most were anthracnose-affected Petit Manseng (1.61%) and white rot-affected Cabernet Sauvignon (44.74%). All diseases-affected Cabernet Sauvignon had much higher titratable acid, a maximum (18.86 g/100 mL) was observed in the gray mold-affected grapes, and only anthracnose-affected grapes with a higher titratable acid level (21.8 g/100 mL) in Petit Manseng. A total of 61 VOCs were identified, including 14 alcohols, 13 esters, 12 aldehydes, 4 acids, 4 ketones, 1 ether, and 13 unknown compounds, which were discussed from different functional groups, such as C6-VOCs, alcohols, ester acetates, aldehydes, and acids. The VOCs of Cabernet Sauvignon changed more than Petit Manseng after infection and gray mold-affected Cabernet Sauvignon changed most. C6-VOCs, including hexanal and (E)-2-hexenal were decreased in all affected grapes. Some unique VOCs may serve as hypothetical biomarkers to help us identify specific varieties of pathogenic fungal infestation.